Pengaruh Pemanfaatan Budaya Lokal Tari Thengul Terhadap Hasil Belajar Dan Keterampilan Sosial Dalam Pembelajaran IPS Bagi Kelas IV Sekolah Dasar - Siti Nikmatur Rohmah; Mustaji; Rr. Nanik Setyowati (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This study aim to determine the effect of using local culture of thengul dance to improve learning outcomes and social skills in social studies learning of fourth grade elementary school students. This research was conducted at SDN Wotanngare I and SDN Wotanngare II in the academic years 2021/2022. This research uses a quantitative approach. This type of research is nonquivalent (pretest and postest) control group design. This study uses 2 class, namely class 4 students at SDN Wotanngare I as the exsperimental class and class 4 students at SDN Wotanngare II as the control class. The research variables were local culture, thengul dance, student learning outcomes and student social skills. The analytical techniques used include normality test, homogeneity test, observation, and Mann-Whithney test. The results showed that the normalized gain value of learning outcomes in the experimental calss was 0,56 and 0,10 in the control class. The results of the Mann-Withney test in the prestest of experimental class and control class were 0,067 which was greater than 0,05. The results of the observation of social skills in the experimental class are 80 % in the complete category. The results of the Mann-Whitney test of the postest in the experimental class and the control class is 0,000. Based on the results of data anlysis, it is concluded that the use of local culture of thengul dance has a significant effect on learning outcomes and social skills of fourth grade elementary school student